Characterization and oncolytic virus targeting of FAP-expressing tumor-associated pericytes in glioblastoma - Ming Li (Acta Neuropathologica Communications, 2020)
Abstract Cancer-associated fibroblasts (CAFs) are activated fibroblasts constituting the major stromal components in many types of cancer. CAFs contribute to hallmarks of cancer such as proliferation, invasion and immunosuppressive tumor microenvironment, and are associated with poor prognosis of patients with cancer. However, in glioblastoma (GBM), the most common and aggressive primary malignant brain tumor, our knowledge about CAFs or CAF-like stromal cells is limited. Here, using commonly accepted CAF markers, we characterized CAF-like cell populations in clinical glioma specimens and datasets along with mouse models of GBM. We found that tumor-associated pericytes marked by co-expression of fibroblast activation protein α (FAP) and PDGFRβ represent major stromal cell subsets in both human GBM and mouse GBM models, while a fraction of mesenchymal neoplastic cells also express FAP in patient tumors. Since oncolytic viruses can kill cancer cells and simultaneously modulate the tumor microenvironment by impacting non-neoplastic populations such as immune cells and tumor vasculature, we further investigated the ability of oncolytic viruses to target GBM-associated stromal cells. An oncolytic adenovirus, ICOVIR15, carrying ∆24-E1A and an RGD-fiber, infects and depletes FAP+ pericytes as well as GBM cells in murine GBM. Our study thus identifies FAP+/PDGFRβ+ pericytes as a major CAF-like stromal cell population in GBM, and highlights the unique property of this oncolytic adenovirus to target both GBM cells and GBM-associated stromal FAP+ cells.